Effects of heat input on the morphology and hardness of hybrid coating - Naping, Rosmia; Maleque, Md. Abdul; Sarifuddin, Norshahida; Hj Hassan, Masjuki; Mohd Zulkifli, Nurin Wahidah (Springer, 2025)
Titanium alloys are extensively used in the aerospace, automotive, and biomedical sectors due to their noteworthy strength. Still, they are sensitive to hightemperature oxidation and hot corrosion, which can diminish their lifespan and limit their application. This study accentuates the influence of varying applied heat input on the microstructural surface features and hardness properties of hybrid environmentally friendly silicon carbide-graphene oxide (eSiC-GO) coating on Ti-alloy using the approach of Liquid Additive Manufacturing (LAM) technique. The eSiC was produced by incorporating waste rice husk as one of the coating materials. The hybrid coating materials were applied onto the Ti-6Al4V substrate and integrated using the TIG torch LAM technique through controlled heat input adjustments, ranging from low to high levels. The result revealed heat input of 768 J/mm produced well-formed of fine dendritic micro-structure due to completely melted of hybrid particles on Ti-alloy and the interphase interaction on XRD analysis. This surface modification enhances the hardness properties by quadruple higher than substrate material up to 1400 Hvkg0.5. This insight provides that developments of the tailored processing parameter is a crucial role in achieving the desired material characteristics, particularly in applications requiring superior mechanical properties and wear resistance.